HUBUNGAN KONDISI SAKIT DENGAN KEJADIAN DEPRESI PADA LANSIA - Dhian Ika Prihananto; Muhammad Mudzakkir (Jurnal EDUNursing, 2023)
Depression is a form of mental disorder which is indicated by symptoms including feeling sad, confused thoughts, hopeless, reduced concentration, loss of interest in doing something, reduced self-esteem and self-confidence, decreased appetite, insomnia, thoughts of suicide and on eventually attempted suicide. Depression is the most common mental disorder in the elderly. The elderly period is marked by the decline of cells due to the aging process which results in weak organs, physical decline, and the emergence of various degenerative diseases. Diseases suffered by the elderly not only have an impact on the occurrence of health problems, but also social and become an economic burden for the elderly because disease treatment requires money. The occurrence of health problems, namely physical illness, is the thing that is most felt by the elderly and affects the depression they experience. The purpose of this study was to determine the relationship between illness and the incidence of depression in the elderly at Blitar Elderly Services in Tulungagung. This research is a mixed method research, case-control study design. The study population is the elderly who experience depression at the Blitar Elderly Service in Tulungagung. The sample consisted of 26 cases and 26 controls which were taken by consecutive sampling. The research instrument was a measurement scale for depression in the elderly (Beck), an interview questionnaire. Data analysis was univariate, bivariate (chi-square). The results of the study were 8 respondents (30.8%) who were sick in the case group and 2 respondents (7.7%) in the control group. The results of the bivariate test (chi-square) obtained p = 0.079, OR = 5.333, 95% CI = 1.008 – 28.209. The conclusion is based on the p value, there is no significant relationship between illness and the incidence of depression in the elderly because the p value = 0.079 > 0.05. Thus it can be said that illness is not a risk factor for depression in the elderly. Keywords: Sick conditions, depression in the elderly, Illness.